Attributes that influence the visitor’s choice in four magical towns in the Mexican northwest - Almendarez-Hernández, Marco Antonio (Universidad Autónoma de Tamaulipas, 2021)
The magical towns concept was devised to increase tourism. It focuses on the dissemination of attractive activities in small towns with historical-cultural attributes that represent the national identity. The objective of this research was to estimate the probability of selecting a certain magical town in northwestern Mexico based on factors such as the user’s profile, their experience, perception and satisfaction of the services and the expenditure made during their stay. The methodology used is based on the Multinomial Logit econometric model and descriptive statistics with control variables was used for its analysis. The survey was administered in four magical towns: Todos Santos and Loreto, from Baja California Sur, and Cosalá and El Rosario, from Sinaloa. Results show that the probabilities of choosing one of them are higher for Todos Santos with 29 %, followed by Cosalá with 28 %, Loreto with 27 % and, finally, El Rosario with 16 %. The variation of the choice is a function of the specificities and characteristics of the destinations. The results of the model will allow the planning and strategies to improve tourist service and promotion in the four magical towns studied, based on the preferences of those who choose these destinations, to attract more visitors.